Research on Dry Coupling Technology in the Ultrasonic Non-Destructive Testing of Concrete - Jun Li; Zeyu Chen (Micromachines, 2025)
In the health monitoring and safety assessments of concrete structures, ultrasonic non-destructive testing (NDT) technology has become an indispensable tool due to its non-destructive nature, efficiency, and precision. However, when used in inspecting irregular concrete surfaces, traditional planar ultrasonic transducers often encounter energy loss and signal attenuation induced by poor interface coupling, which significantly reduces the accuracy and reliability of the test results. To address this problem, this article proposes a point-contact dry coupling ultrasonic transducer solution, which enables efficient acquisition of ultrasonic signals within concrete without the need for couplants. By combining an array imaging system with a total focusing algorithm, this study not only significantly enhances the convenience and signal-to-noise ratio (SNR) of concrete ultrasonic imaging, but also opens new pathways for ultrasonic NDT technology in concrete.